The Effect of Biomechanics Information on Driver Swing Learning of Intermediate Golfers - Song-Yi Choi; Sang-Hyun Kwon; Dong-Won Yook (Korea Institute of Sport Science, 2023)
PURPOSE This study investigates the effectiveness of biomechanics information on intermediate golfers driver swing learning. It analyzes changes in center of pressure (COP) patterns, GRF Direction Inclination, driver performance, and learners psychological responses to determine the learning effects. METHODS Subjects were 32 right-handed male golfers (handicap 15-23) who had no difficulty in performing the golf driver swing (Full swing). Four groups were selected, BF (Biomechanics Feedback group), BVC (Biomechanics Verbal Cue group), CB (Combination group), and CT (Control group), and assigned randomly. Driver swing learning showed results after 6 weeks,and a transfer test was conducted 1 week after the completion of the learning. RESULTS Analysis of COP patterns and GRF Direction Inclination indicated changes in the BF, BVC, and CB groups. Furthermore, analysis of driver distance (m), club head speed (km/h), and ball spin rate (rpm) revealed that during the 6-week acquisition phase, all three groups (excluding the control group) showed improvements in driver distance, club head speed, and ball spin rate. However, there were no statistically significant differences among the groups. In contrast, the transfer test showed statistically significant differences among the groups, with the CB group exhibiting the highest driver distance. Learners' psychological responses during the learning process were trust, understanding, and satisfaction. The understanding factor was relatively higher in the CB and BVC groups compared to the BF group. CONCLUSIONS In summary, biomechanics information (BI) was effective in improving driver performance, and changesappeared in the COP pattern and GRF Direction Inclination, indicating a change in movement. Therefore, BI can be fully utilized for athletes or high-level advanced players and for motor learning for intermediate-level students.However, BI can only improve learning effects by strengthening learners' "understanding" when visual feedback forms and verbal cues are provided together.